PENERAPAN MODEL GAMIFIKASI PADA APLIKASI GAME PENDIDIKAN PANCASILA BERBASIS MULTIMEDIA ANIMASI 2D - Putri, Risanty Amelia; Wahyu, Sawali (Universitas Budi Luhur, 2025)
Improving the quality of human resources depends on education. However, the low quality of education in Indonesia is often caused by factors such as lack of facilities and infrastructure, high education costs, and unequal educational opportunities. At MI Al-Ihsan, the low learning outcomes of students in Pancasila Education are largely due to the large amount of material and theory that requires students to memorize a lot, then the lack of creativity and innovation in the teaching methods applied by teachers, which tend to be monotonous and uninteresting for students because the facilities and infrastructure are still inadequate. To overcome this problem, technology can be utilized through the application of gamification in learning media. This game is designed to attract students' interest by matching images with time limits, lives, scores, and leaderboards as well as learning materials that are in accordance with the curriculum. The methodology used in developing this application is the Multimedia Development Life Cycle (MDLC) and the application of gamification. The test results using the SUS (System Usability Scale) method obtained a score of 84.7, which means getting an A or Excellent grade. The results of the study showed that learning using game media such as gamification can make learning more interesting and effective. Students become more motivated and interested in studying Pancasila education materials which ultimately improves their learning outcomes.